THE EFFECT OF KEPOK BANANA PEEL EXTRACT (Musa acuminate balbisiana Colla) AND BAP ON THE GROWTH OF RED POTATO PLANLETS (Solanum tuberosum L.) IN VITRO - Edi, Syahmi; Parhusip, Tiropa Oktavia; Panggabean, Nurul Huda (JURNAL BIOSAINS, 2024)
This research aims to determine the effect of from kepok banana peel extract (Musa acuminata balbisiana Colla) and BAP and their interaction on the growth of red potato plantlets (Solanum tuberosum L.) in vitro. This research was conducted in September-October 2023 at the G10 Agrotech Medan Plant Tissue Culture Laboratory Jl. Sei Bahorok No. 47 F Medan Baru. This research used a factorial Completely Randomized Design (CRD) with two factors. The first factor is the concentration of Kepok banana peel extract in 3 levels, namely (0, 25 and 50 g/L) and the second factor is BAP which consists of 4 levels, namely (0, 0.5, 1 and 1.5 mg/L). 12 treatment combinations were obtained and each treatment was repeated 3 times to obtain 36 experimental units. The research parameters were plantlet height, number of shoots, number of leaves and number of roots analyzed using Analysis of Variance (ANOVA) and if they were significantly different, further tests would be carried out using the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the treatment of kepok banana peel extract and BAP had a significant effect on plantlet height, number of shoots, number of leaves and number of roots. The highest average plantlet height was produced by banana peel extract 50gr/L (7.60 cm), BAP 1mg/L (6.70 cm). The highest number of shoots was produced by banana peel extract 50gr/L (6.33 shoots), BAP 1.5 mg/L (6.33 shoots). The highest number of leaves was produced by sweet corn extract 25 gr/L, namely (10.00 leaves), BAP 0.5 mg/L as much as (8.00 leaves). The highest number of roots was produced by the 50gr/L sweet corn extract treatment, namely (12.00 roots), the highest number of roots was produced by BAP 1 mg/L, namely (7.33 roots). The highest average plantlet height, number of shoots and leaves were produced by the A2B1 treatment interaction, namely 7.40 cm plantlet height, 6.33 shoots and 16.33 leaves. The highest number of roots was produced by the A2B2 treatment interaction, namely 8.67 roots.  This is an open-access article under the CC-BY-SA license